1994
DOI: 10.1177/004728759403200406
|View full text |Cite
|
Sign up to set email alerts
|

Using Inferential Evidence to Determine Likely Reaction to a Price I ncrease at a Festival

Abstract: This article reports an attempt to use an inferential approach to assess the likely reaction of festival visitors to a price increase. Reactions were evaluated from a historical analysis of visitation reaction to price increases and responses to six questions pertaining to substi tution opportunities, strength of reference price, distribution of trip costs, affluence of the target market, and value for money. As a result of the findings, a decision was made to raise the admission price by one-third.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Rather than considering only the benefit they can derive from an item, shoppers consider how the item's current price compares to its usual price. This effect of consumers' conceptions of usual prices (termed 'reference prices') has been found to influence travel decisions as well: Crompton and Love (1994) found that people tend to avoid a festival if the cost of attending appears to be higher than the cost of attending other festivals. This suggests that reference prices contaminate the data gathered in travel-cost methods.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than considering only the benefit they can derive from an item, shoppers consider how the item's current price compares to its usual price. This effect of consumers' conceptions of usual prices (termed 'reference prices') has been found to influence travel decisions as well: Crompton and Love (1994) found that people tend to avoid a festival if the cost of attending appears to be higher than the cost of attending other festivals. This suggests that reference prices contaminate the data gathered in travel-cost methods.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a body of tourism research that has focused on the psychological impact of prices (Al-Sabbahy, Ekinci, and Riley 2004;Crompton and Love 1994;Lawson, Gnoth, and Paulin 1995). In this context, the idea of potentially asymmetric responsiveness to prices derived from the existence of reference points (i.e., price loss aversion) is especially relevant as the increased promotional activity by competing destinations is likely to raise price elasticities (Crouch 1994) and, as Kim and Crompton (2002) indicate, the challenge is to find ways to reduce individuals' reluctance to accept increases in price.…”
Section: Introductionmentioning
confidence: 99%
“…Response options ranged from ''completely unfair'' (scored 0) to ''completely fair'' (scored 10). The wording of this item is similar to wording used in previous research (Crompton, 1984;Crompton & Love, 1994;Kahneman et al, 1976;Kyle et al, 2002).…”
Section: Measurementmentioning
confidence: 99%
“…Equity theory presents an opportunity to address this issue. Traditional research on admission price has focused on economic determinants of perceiving a given price (Crompton & Kim, 2001;Crompton & Love, 1994;Crompton & Lue, 1992;Kim & Crompton, 2002), and identifying concept such as perceptions of fairness, justice or willingness to pay (Adams, 1963;Ajzen & Driver, 1992;Folger & Konovsky, 1989;Greenberg, 1986;McCarville et al, 1996;Markovsky, 1988). However, this study examines an integration of a number of concepts including users' judgments of procedural justice and distributive justice, perception of fair price, social equity, and price acceptability of user fees.…”
Section: Introductionmentioning
confidence: 99%